2019
DOI: 10.1021/acs.macromol.9b01252
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Triggered Self-Reporting Release of Nitric Oxide (NO) for Bacterial Biofilm Dispersal

Abstract: Bacterial infection poses a massive threat to our society, and bacterial biofilm is a major cause of chronic and recurrent infections. The treatment of bacterial biofilms represents a challenging task, and the development of antibacterial materials that can not only disperse bacterial biofilms but also kill bacteria is of increasing interest. Herein, we report the fabrication of well-defined nitric oxide (NO)-releasing amphiphiles, poly­(ethylene oxide)-b-polyCouNO (PEO-b-PCouNO), where CouNO is an N-nitrosoam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 56 publications
0
61
0
Order By: Relevance
“…N -nitrosoamine-based NO donors are also photo-triggered NO donors and several small molecular N -nitrosoamine-based NO donors have been explored [141,142,143,144,145]. More recently, Hu et al reported a NO releasing micelle bearing visible light responsive NO donors [146]. Unlike the conventional preparation of NO releasing polymers which usually need postmodification approaches, controlled chain length of N -nitrosoamine-based NO releasing monomers were polymerized by utilizing RAFT polymerization with a polyethylene glycol modified chain transfer agent.…”
Section: No Releasing Polymeric Materials For Antibacterial Applicmentioning
confidence: 99%
See 1 more Smart Citation
“…N -nitrosoamine-based NO donors are also photo-triggered NO donors and several small molecular N -nitrosoamine-based NO donors have been explored [141,142,143,144,145]. More recently, Hu et al reported a NO releasing micelle bearing visible light responsive NO donors [146]. Unlike the conventional preparation of NO releasing polymers which usually need postmodification approaches, controlled chain length of N -nitrosoamine-based NO releasing monomers were polymerized by utilizing RAFT polymerization with a polyethylene glycol modified chain transfer agent.…”
Section: No Releasing Polymeric Materials For Antibacterial Applicmentioning
confidence: 99%
“…Fabrication of visible light responsive micelles, and the co-release of NO and Cip under irradiation of 410 nm light to concurrently disperse biofilms and kill bacteria. Reproduced with permission from [146]. Copyright 2019, American Chemical Society.…”
Section: Figurementioning
confidence: 99%
“…A recent report by Hu and Yu et al described a new, distinct type of NO donor based on a photoresponsive coumarincontaining monomer, whose secondary amine moiety could be loaded with NO upon treatment with the gaseous biocide. 193 The monomer could be directly polymerized in a RAFT chain extension process, starting from a poly(ethylene glycol) macro chain transfer agent, to form amphiphilic block copolymers. These formed selfassembled micelles with NO-loaded hydrophobic cores in aqueous solution.…”
Section: Multi-action Antibiofilm Materialsmentioning
confidence: 99%
“…Along with these, many studies were also carried out to explore novel methods for NO delivery, such as incorporating NO donors into nanoparticles and polymer coating (Sadrearhami et al 2017 ; Duong et al 2014a ; Nablo and Schoenfisch 2003 ; Nablo et al 2005 ). However, more often than not these studies tested different concentrations of NO donors towards early stage biofilms formed by type strains, or did not specify optimal treatment time which is crucial for the interpretation of data from young biofilms to distinguish between prevention and dispersal (Barraud et al 2009a ; Barnes et al 2013 ; Sadrearhami et al 2017 ; Duong et al 2014a ; Shen et al 2019 ; Duong et al 2014b ; Zhu et al 2018 ; Marvasi et al 2014 ). To this end, we systematically compared the optimal concentrations and treatment time of 7 NO donors for triggering biofilm dispersal using P. aeruginosa PAO1, including SNP, S-nitroso-glutathione (GSNO), S-nitroso-N-acetyl-DL-penicillamine (SNAP), 1-(hydroxy-NNO-azoxy)-L-proline (PROLI NONOate), 6-(2-hydroxy-1-methyl-2-nitrosohydrazino)-N-methyl-1-hexanamine (MAHMA NONOate), (Z)-1-[N-[3-aminopropyl]-N-[4-(3-aminopropylammonio)butyl]-amino]diazen-1-ium-1,2-diolate (Spermine NONOate) and diethylammonium (Z)-1-(N,N-diethylamino)diazen-1-ium-1,2-diolate (DEA-NONOate).…”
Section: Introductionmentioning
confidence: 99%